The jazz standards a guide to the repertoire - Gioia, Ted (Oxford Oxford University Press, 2012)
This comprehensive guide tells the story of more than 250 key jazz songs and includes a listening guide to more than 2,000 recordings. The author draws on his deep personal experience with jazz music to outline the history and significance of the compositions and tell how they have been performed by different generations of jazz artists.
After You've Gone -- Ain't Misbehavin' -- Airegin -- Alfie -- All Blues -- AH of Me -- All of You -- All the Things You Are -- Alone Together -- Angel Eyes -- April in Paris -- Autumn in New York -- Autumn Leaves -- Bags' Groove -- Basin Street Blues -- Beale Street Blues -- Bemsha Swing -- Billie's Bounce -- Blue Bossa -- Blue in Green -- Blue Monk -- Blue Moon -- Blue Skies -- Bluesette -- Body and Soul -- But Beautiful -- But Not for Me -- Bye Bye Blackbird -- C Jam Blues -- Cantaloupe Island -- Caravan -- Chelsea Bridge -- Cherokee -- A Child Is Bom -- Come Rain or Come Shine -- Come Sunday -- Con Alma -- Confirmation -- Corcovado -- Cotton Tail -- Darn That Dream -- Days of Wine and Roses -- Desafmado -- Dinah -- Django -- Do Nothin' Till You Hear from Me -- Do You Know What It Means to Miss New Orleans? -- Donna Lee -- Don't Blame Me -- Don't Get Around Much Anymore -- East of the Sun (and West of the, Moon) -- Easy Living -- Easy to Love -- Embraceable You -- Emily -- Epistrophy -- Everything Happens to Me -- Evidence -- Ev'ry Time We Say Goodbye -- Exactly Like You -- Falling in Love with Love -- Fascinating Rhythm -- Fly Me to the Moon -- A Foggy Day -- Footprints -- Gee, Baby, Ain't I Good to You? -- Georgia on My Mind -- Ghost of a Chance -- Giant Steps -- The Girl from Ipanema -- God Bless the Child -- Gone with the Wind -- Good Morning Heartache -- Goodbye Pork Pie Hat -- Groovin' High -- Have You Met Miss Jones? -- Here's That Rainy Day -- Honeysuckle Rose -- Hot House -- How Deep Is the Ocean? -- How High the Moon -- How Insensitive -- How Long Has This Been Going On? -- I Can't Get Started -- I Can't Give You Anything but Love -- I Cover the Waterfront -- I Didn't Know What Time It Was -- I Fall in Love Too Easily -- I Got It Bad (and That Ain't Good) -- I Got Rhythm -- I Hear a Rhapsody -- I Let a Song Go Out of My Heart -- I Love You -- I Mean You -- I Only Have Eyes for You -- -- I Should Care -- I Surrender, Dear -- I Thought about You -- I Want to Be Happy -- If You Could See Me Now -- I'll Remember April -- I'm in the Mood for Love -- Impressions -- In a Mellow Tone -- In a Sentimental Mood -- In Your Own Sweet Way -- Indiana -- Invitation -- It Could Happen to You -- It Don't Mean a Thing (If It Ain't Got That Swing) -- It Might as Well Be Spring -- I've Found a New Baby -- The Jitterbug Waltz -- Joy Spring -- Just Friends -- Just One of Those Things -- Just You, Just Me -- King Porter Stomp -- Lady Bird -- The Lady Is a Tramp -- Lament -- Laura -- Lester Leaps In -- Like Someone in Love -- Limehouse Blues -- Liza -- Lonely Woman -- Love for Sale -- Lover -- Lover, Come Back to Me -- Lover Man -- Lullaby of Birdland -- Lush Life -- Mack the Knife -- Maiden Voyage -- The Man I Love -- Manha de Carnaval -- Mean to Me -- Meditation -- Memories of You -- Milestones -- Misterioso -- Misty -- Momenf s Notice -- Mood Indigo -- More Than You Know -- Muskrat Ramble -- My Favorite Things -- My Foolish Heart -- My Funny Valentine -- My Old Flame -- My One and Only Love -- My Romance -- Naima -- Nardis -- Nature Boy -- The Nearness of You -- Nice Work If You Can Get It -- Night and Day -- Night in Tunisia -- Night Train -- Now's the Time -- Nuages -- Oh, Lady Be Good! -- Old Folks -- Oleo -- On a Clear Day -- On Green Dolphin Street -- On the Sunny Side of the Street -- Once I Loved -- One Note Samba -- One o'clock Jump -- Ornithology -- Our Love Is Here to Stay -- Out of Nowhere -- Over the Rainbow -- Peace -- The Peacocks -- Pennies from Heaven -- Perdido -- Poinciana -- Polka Dots and Moonbeams -- Prelude to a Kiss -- Rhythm-a-ning -- 'Round Midnight -- Royal Garden Blues -- Ruby, My Dear -- -- St. Louis Blues -- St. Thomas -- Satin Doll -- Scrapple from the Apple -- 60 Secret Love -- The Shadow of Your Smile -- Shine -- Skylark -- Smile -- Smoke Gets in Your Eyes -- So What -- Softly, as in a Morning Sunrise -- Solar -- Solitude -- Someday My Prince Will Come -- Someone to Watch over Me -- Song for My Father -- The Song Is You -- Sophisticated Lady -- Soul Eyes -- Speak Low -- Spring Can Really Hang You Up the Most -- Spring Is Here -- Star Dust -- Star Eyes -- Stella by Starlight -- Stolen Moments -- Stompin' at the Savoy -- Stormy Weather -- Straight, No Chaser -- Struttin' with Some Barbecue -- Summertime -- Sweet Georgia Brown -- 'S Wonderful -- Take Five -- Take the A Train -- Tea for Two -- Tenderly -- There Is No Greater Love -- There Will Never Be Another You -- These Foolish Things -- They Can't Take That Away from Me -- Things Ain't What They Used to Be -- Tiger Rag -- Time after Time -- Tin Roof Blues -- The Very Thought of You -- Waltz for Debby -- Watermelon Man -- Wave -- The Way You Look Tonight -- Well, You Needn't -- What Is This Thing Called Love? -- What's New? -- When the Saints Go Marching In -- Whisper Not -- Willow Weep for Me -- Yardbird Suite -- Yesterdays -- You Don't Know What Love Is -- You Go to My Head -- You Stepped Out of a Dream -- You'd Be So Nice to Come Home To.
Includes bibliographical references, discographical references, and index.
Keywords: Jazz -- Bibliography; Jazz -- Discography; Jazz -- Analysis, appreciation